An evaluation of the potential effectiveness of tobacco-related health messages among Inuit in Nunavut, Canada: What types of messages work best at promoting smoking cessation among Inuit smokers? - Costello, Mary-Jean (University of Waterloo, 2013)
Background. Inuit experience some of the highest rates of tobacco use and of tobacco-related diseases in Canada. Communication strategies, such as health warnings on tobacco products, are seen as a necessary means of informing the public of tobacco-related health risk and motivating smokers to want to quit smoking. However, there is little evidence to suggest how such strategies might be working among Inuit nor is there evidence to suggest how best to communicate tobacco-related health risk to and promote smoking cessation among Inuit smokers. Objectives. (1) To systematically examine the effects of textual message frame (i.e., loss- vs. gain-framed), graphic type (i.e., gruesome vs. personal suffering), and narrative style (i.e., testimonial vs. didactic) on measures of message acceptance (i.e., personal relevance and perceived credibility), affective response, and potential message effectiveness. (2) To examine fear as a potential mediator of the relation between textual message frame and measures of potential message effectiveness, as well as of the relation between graphic type and measures of potential message effectiveness. (3) To examine the potential impact of the message spokesperson (i.e., Caucasian, middle-aged male/female vs. Inuit middle-aged male/female vs. Inuit Elder male/female) on measures of message acceptance and potential message effectiveness. Experimental design. A repeated measures (i.e., within-subject) 2 x 2 x 2 factorial design was used to examine the effects of textual message frame, graphic type and narrative style. A separate ranking task assessed the potential impact of the message spokesperson. Methods. Eligible participants (Inuit, aged 18 years of age or older, having smoked at least one cigarette in the previous 30 days and smoked over 100 cigarettes in their lifetime) were recruited in October 2012 from two communities in Nunavut (Iqaluit and Rankin Inlet). Participants completed a survey, an experimental procedure (i.e., a health warning rating task) and a health warning ranking task on a hand-held electronic device with a trained research assistant. With data from the health warning rating task, a series of multinomial regression models using the Generalized Estimating Equation (GEE) method were fitted to examine the effects of three message characteristics on each of the outcome measures, controlling for known covariates. Outcome measures were categorized into 3-levels: (1) extremely, (2) somewhat, and (3) not really. The “not really” category was used as the comparison category for multinomial regression models. Multinomial regression was also used to examine the potential mediating effects of fear as it related to each of the measures of potential message effectiveness. With data from the health warning ranking task, frequencies of participant choices as related to the message spokesperson were examined. 129 participants were included in the analyses. Results. Participants were, on average, 37.3 years of age (STD = 12.7) and smoked 13.0 cigarettes per day (STD = 8.9). Just over half were female (56.6%) and most had less than a high school education (72.7%). Messages with gruesome images were more likely than those with images of personal suffering to be rated as extremely relevant (OR = 2.23, CI: 1.56-3.20), credible (OR = 2.46, CI: 1.67-3.62), emotionally arousing (OR = 3.40, CI: 2.27-5.08), and potentially effective (OR = 2.56, CI: 1.69-3.86). Loss-framed messages were more likely than gain-framed messages to be rated as extremely emotionally arousing (OR = 1.71, CI: 1.23-2.37), but no more likely to be rated as extremely relevant (OR = 1.03, CI: 0.61-1.74), credible (OR = 1.06, CI: 0.81-1.39), or potentially effective (OR = 1.24, CI: 0.98-1.58). Testimonial messages were no more likely than didactic messages to be rated as extremely relevant (OR = 0.90, CI: 0.60-1.35), credible (OR = 0.97, CI: 0.70-1.34), emotionally arousing (OR = 1.22, CI: 0.90-1.67), or potentially effective (OR = 1.08, CI: 0.85-1.37). Fear appeared to partially mediate the relation between textual message frame and all three indicators of potential message effectiveness suggesting loss-framed messages elicited greater feelings of fear, thereby enhancing the potential effectiveness of the message. There was also some evidence that fear partially mediated the relation between graphic type and some indicators of potential message effectiveness suggesting messages with gruesome images elicited greater feelings of fear, thereby enhancing the potential effectiveness of the messages. Finally, greater proportions of participants indicated health warnings with an Inuit Elder were most personally relevant (44.2%) and most credible (35.9%) compared to health warnings with middle-aged Inuit or Caucasian spokespersons. However, participants’ choice of which health warning was potentially most effective was split relatively evenly between all options. Conclusions. Findings from this study suggest health warnings accompanied by gruesome images are potentially more effective at communicating tobacco-related health risk and motivating cessation among Inuit compared to those with images of personal suffering. This provides some initial evidence that current communication strategies that use gruesome imagery, like some tobacco product health warnings in Canada, may be effective among Inuit populations. However, when a spokesperson is used in a communication campaign, Inuit Elders tend to be preferred. Together these findings suggest that an integrated communication strategy that includes complementary, targeted materials working synergistically alongside population-level approaches (like tobacco product warning labels) may work best among Inuit.
Keywords: Tobacco; Inuit; Communication; Health; Health Studies and Gerontology